Git essentials for beginners. (Packt Publishing, 2022)
Your one-stop destination for everything you need to know about Git. About This Video Understand how Git works and master the essentials Learn about merging types and stashing Understand Git log filtering, merge conflicts, and searching In Detail Version Control has always been part of the software development lifecycle to facilitate programmers to restore the previous versions and assist with release management. Git is a popular open-source distributed version control software and manages hundreds of branches with hundreds of programmers very efficiently. This course includes the following three mini-courses to give you a wholesome experience: Git essentials Merging types, branching type, stash, and rebase Searching, rewriting, history, and reset We will start with Git installation and learn all the fundamentals in a step-by-step approach. We will also cover Git architecture, which is fundamental in understanding Git. This will be followed by creating Git repositories and adding, changing, and deleting files. You will learn to commit changes to Git, compare commits, and review commit logs. We will also discuss how to undo changes and ignore files based on name, regular expression, and folder name. Finally, you will learn to use the git log command efficiently to filter the commit log. By the end of the course, you will gain a strong understanding of the fundamentals of Git, which will also aid in understanding GitHub, BitBucket, and so on. Audience This course is for cloud engineers, DevOps engineers, and architects. Developers, programmers, software managers, and modern operations managers can also take up this course to upskill them.